Antioxidant and Quality Effects of Red Grape Pomace in Barbecued Pork Burgers: Implications for PAH Formation - María Jesús Petrón; María Jesús Martín-Mateos; Miriam Sánchez-Ordóñez; Belén Godoy; María Rosario Ramírez-Bernabé (Antioxidants)
The growing concern over the presence of polycyclic aromatic hydrocarbons (PAHs) in grilled meats has intensified the search for natural mitigation strategies. This study evaluates the effect of red grape pomace (RGP), a natural by-product with antioxidant properties, on the lipid stability, color, fatty acid profile, volatile compounds, and PAHs formation in barbecued pork burgers. Unlike previous studies focusing on polyphenol extracts, this work investigates, for the first time, the direct incorporation of whole RGP stabilized by high hydrostatic pressure (HHP), a method that preserves its bioactive profile and ensures food safety. Incorporation of RGP at different levels (0.5%, 1%, and 3%) demonstrates its potential as a functional ingredient in meat products. Our results show that RGP effectively inhibits lipid oxidation, as indicated by significantly lower malondialdehyde (MDA) levels (p < 0.001) compared to control batches. It also modified the fatty acid profile by reducing saturated fatty acids and increasing the linoleic acid content (up to 15.56% at the 3% level). As the RPG concentration increased, color parameters (lightness, redness, yellowness, chroma, and hue) decreased significantly (p < 0.001), particularly at higher pomace levels (1% and 3%). The RGP did not significantly affect the PAH concentration, indicating its safe use in barbecued products. However, it selectively influenced volatile compounds, decreasing the hydrocarbon levels at higher concentrations, likely due to its antioxidant properties. These findings suggest that stabilized RGP may serve as a natural additive that enhances the nutritional quality and reduces lipid oxidation, without promoting PAH formation in thermally processed meats.